Identification of Factors Causing Hypertension in Outpatients Department at Petarukan Public Health Center, Pemalang Regency - Wanda Aisah Dwi Putri; Dian Kartikasari (Prosiding University Research Colloquium, 2022)
Background : Hypertension is one of the causes of death worldwide. People with hypertension are at high risk of heart disease and suffer from other disorders involving nerves, kidneys, and blood vessels. Understanding the characteristics and various factors related to hypertension will be very helpful in early detection to reduce the incidence of hypertension. Objective : This study aims to identify the characteristics of hypertensive patients and the risk factors that cause hypertension. Sample : An accidental sampling was used with a total of 146 respondents Methods : A descriptive study was used in this study. Data were collected using a questionnaire to analyze factors causing hypertension, a blood pressure monitor, and weight scales. Results : This study showed that the characteristics of hypertensive patients were in the age range of 56-65 years, female, basic education, and housewives. The risk factors that cause hypertension includes high salt consumption, obesity, lack of physical activity, heredity, moderate smokers (for male respondents), and most of the respondents do not consume alcohol. Conclusion : This study is expected to be a reference for primary health care to improve health promotion related to factors that influence hypertension and prevent hypertension by controlling blood pressure regularly.